On the Brazilian Exocnophila stick insects (Insecta: Phasmatodea), with the description of a new species - Ghirotto, Victor Morais; Conle, Oskar; Hennemann, Frank; Valero, Pablo; Cancello, Eliana M. (Zootaxa, 2024)
Several stick insects occurring in Brazil belong to the Diapheromerinae. Before this work, the Brazilian genus Exocnophila contained three species known only from females, Exocnophila exintegra Zompro, 2001, Exocnophila tuberculata (Brunner von Wattenwyl, 1907) and Exocnophila cornuta (Brunner von Wattenwyl, 1907). Based on recently collected material, we found that the males of Exocnophila are assigned to another genus in the Diapheromerinae, the heterogeneous Bacteria. Here we show that the type species Exocnophila exintegra Zompro, 2001 syn. nov. is a junior synonym of Bacteria brevitarsata Brunner von Wattenwyl, 1907, which is transferred and redescribed as Exocnophila brevitarsata comb. nov.. We also transfer and redescribe Bacteria hastata as Exocnophila hastata comb. nov. and propose a new species, Exocnophila ovifuscum sp. nov., from Rio de Janeiro state, Brazil, with descriptions of females, males and eggs. We provide the first biological observations for the genus and a short discussion about its relationships.